Cardioprotective measures in patients with cardiovascular risk factors and polymorbidity - article Editorial (Лечащий Врач, 2022)
4th international educational forum «Russian Days of the Heart» took place in St. Petersburg, 22 June 2022. Its program included a satellite symposium «Actual cardioneurology: cardiovascular risk factors and polymorbidity» that was held with the support of the «Grindex» company. Therapeutic arsenal in the context of cardioprotection is represented by a relatively large number of drugs, among which the greatest attention was paid to piperazine derivatives (ranolazine etc.) and gamma-butyrobetaine hydroxylase inhibitors (Mildronate): the evidence base, indications and pharmacodynamics. Pathogenetic features of comorbidity determine the basic principles of the treatment of cardiovascular diseases in patients with type 2 diabetes. Partial fatty acid oxidation (pFOX) inhibitors (ranolazine, trimetazidine, meldonium) are indicated as cardiac cytoprotectors for this group of patients. Nervous system affected by type 2 diabetes was also issued. Drugs that can be used to slow the progression of diabetic neuropathy are ipidacrine and meldonium. As a final report, the results of the study «Asthenic disorders in patients of a cardiologist and neurologist – in the wake of one study» were presented. Due to the multidisciplinary nature of reports the speakers were able to comprehend a complex comorbid patient at all stages of the cardiovascular disease continuum, as well as demonstrate numerous possibilities for the therapeutic correction of cardiovascular disorders, including through Mildronate pharmacodynamics and broad indications.